Unitarian Universalist Church of Fresno "Love is a Magic Pony" and Cupcake Making - Watkins, Howard::::::::: (1988)
Children and adults preparing to make cupcakes; Susan Holland, Juanita Temple, Doris Stevens, Richard Howard, ?, Adam Watkins (red shirt), Louise Richardson, and ??